Разработка и эксплуатация серийных энергетических ГТУ на магнитных подшипниках - Ануров, Ю. М.; Литвинов, Е. В. (Eastern-European Journal of Enterprise Technologies, 2009)
Features of application of electromagnetic bearings in gas-turbine power plant to installation, and also results of research of their working capacity in power units are considered. Are brought mass-dimensional characteristics wire-shaft, the engine including rotors and a turbogenerator. The design of system and feature of its debugging is described